Dogged - Gnall, Stacy, 1983- (Juniper Prize for Poetry., 2022)
"Located somewhere between fiction and reality, the animals of Dogged exist as both 'creatures children see in their fevers' and 'your one / good dream / in the night.' Inhabiting a space apart from time and narrative, the space of the ever-elusive now, these haunting poems probe animal consciousness and desire, as 'howls float / like crocuses- / violet / and half open / to the unknown.' Looking to a wide range of high and low visual media, from Steven Spielberg's Jaws and Animal Planet's Fatal Attractions to Peter Paul Rubens's painting of Hercules's dog discovering Tyrian purple, Stacy Gnall ponders human-animal connections and divisions, exploring those moments when human voices blend with 'silent' beasts to exceed the limits of language. In Dogged, animals emerge as the highest aspiration of poetry"--